SISTEM PELAYANAN PEMBUATAN e-KTP TERHADAP MASYARAKAT SIBERUT TENGAH KABUPATEN KEPULAUAN MENTAWAI - Ricky Hedman Erik; Yohanis (Jurnal Administrasi Publik dan Pemerintahan, 2022)
This research was conducted to find out the E-KTP manufacturing service system provided by the government of Central Siberut District of Mentawai Islands Regency which is measured through several service system indicators, namely: direct evidence, empathy, responsiveness, reliability and communication, in addition this research is also conducted to find out the constraint factors of the E-KTP manufacturing service system that can be seen from facilities and infrastructure,  In service procedures and employee capabilities, the study uses a qualitative descriptive approach with data collection obtained from observations and interviews. The results of this study show that the service system for making E-KTP in The Central Siberut District of Mentawai Islands Regency is still not maximal which can be seen from the assurance of uncertain services, inadequate facilities and infrastructure, lack of attention and good response from employees, poor employee response and lack of information provided to the public about the procedures of the E-KTP manufacturing service system. The author suggested that the Government of Central Siberut Subdistrict improve employee performance by training employees, adding facilities and infrastructure and also clarifying information about E-KTP manufacturing service procedures.